Acute myocardial infarction: a literature review - Prata Sobrinho, José Renaldo (2017)
The study was developed through bibliographic research, performed at UniAges´s labs. The analysis and the writing of the paper were carried out during the semester 2015-1 for the third period of Nursing class. Myocardial infarction is a myocardial ischemic injury muscle due to lack of blood flow, oxygenation consequently. Disease severity refers the need for new studies and research to clarify and contribute to reduction of index cases, since there is a high prevalence of mortality and morbidity. Undoubtedly only the control of risk factors for acute myocardial infarction can be effective in decreasing mortality rates from cardiovascular causes. Importantly, healthy habits should be maintained throughout life, to protect people from new events. The immediate patient care increases the chances of survival and recovery with minimal consequences.